Database Benchmarking and Stress Testing An Evidence-Based Approach to Decisions on Architecture and Technology - Scalzo, Bert (Apress, 2018)
Provide evidence-based answers that can be measured and relied upon by your business. Database administrators will be able to make sound architectural decisions in a fast-changing landscape of virtualized servers and container-based solutions based on the empirical method presented in this book for answering "what if" questions about database performance. Today's database administrators face numerous questions such as: What if we consolidate databases using multitenant features? What if we virtualize database servers as Docker containers? What if we deploy the latest in NVMe flash disks to speed up IO access? Do features such as compression, partitioning, and in-memory OLTP earn back their price? What if we move our databases to the cloud? As an administrator, do you know the answers or even how to test the assumptions? Database Benchmarking and Stress Testing introduces you to database benchmarking using industry-standard test suites such as the TCP series of benchmarks, which are the same benchmarks that vendors rely upon. You'll learn to run these industry-standard benchmarks and collect results to use in answering questions about the performance impact of architectural changes, technology changes, and even down to the brand of database software. You'll learn to measure performance and predict the specific impact of changes to your environment. You'll know the limitations of the benchmarks and the crucial difference between benchmarking and workload capture/reply. This book teaches you how to create empirical evidence in support of business and technology decisions. It's about not guessing when you should be measuring. Empirical testing is scientific testing that delivers measurable results. Begin with a hypothesis about the impact of a possible architecture or technology change. Then run the appropriate benchmarks to gather data and predict whether the change you're exploring will be beneficial, and by what order of magnitude. Stop guessing. Start measuring. Let Database Benchmarking and Stress Testing show the way. What You'll Learn: Understand the industry-standard database benchmarks, and when each is best used Prepare for a database benchmarking effort so reliable results can be achieved Perform database benchmarking for consolidation, virtualization, and cloud projects Recognize and avoid common mistakes in benchmarking database performance Measure and interpret results in a rational, concise manner for reliable comparisons Choose and provide advice on benchmarking tools based on their pros and cons.